Front Cover: Volume 25 Issue 3. (20th May 2022) - Parkinson, Anne; Brunoro, Crystal; Leayr, Jack; Fanning, Vanessa; Chisholm, Katrina; Drew, Janet; Desborough, Jane; Phillips, Christine
Abstract : Cover Caption : The cover image is based on the Review Article Intertwined like a double helix: A meta-synthesis of the qualitative literature examining the experiences of living with someone with multiple sclerosis by Anne Parkinson et al., https://doi.org/10.1111/hex.13432 .